The Phenomenon of Death in Al-Mutanabbi's Poetry (Islamic Sciences Journal, 2023)
ABSTRACT              This study examines the topic of death in the poetry of Abi al-Tayyib al-Mutanabi. Death became a preoccupation that terrified the poet and continued throughout his lifetime. Al-Mutanabbi died a terrible death at the hands of a small band of criminals commanded by Fatik, who crushed his grandest aspirations.The researcher argues that al- Mutanabbi and poetry are dominated by pessimism, which is accompanied with transcendence, ambiguity, and a desire for future greatness so as to compete with monarchs and princes. These characteristics accelerated his demise.
Keywords: Poetry, Al-Mutanabbi, death, pessimism, mystery, praiseworthy, camphor, human.